2021
DOI: 10.1111/jfb.14613
|View full text |Cite
|
Sign up to set email alerts
|

Angel sharks (Squatinidae): A review of biological knowledge and exploitation

Abstract: Angel sharks (Squatina spp.) are distributed in warm temperate to tropical waters around the world. Many species occur in shelf seas and exhibit seasonal inshoreoffshore migrations, moving inshore to give birth. Consequently, there can be high spatial overlap of angel shark populations with fisheries and other human activities. Their dorso-ventrally flattened body shape, large size (most species attain >100 cm total length, L T) and demersal nature means that they may be taken in a variety of demersal fishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 154 publications
(197 reference statements)
2
31
0
Order By: Relevance
“…Angel sharks often occupy coastal waters and thus exposed to different contaminants, the high trophic level of this environment could increase the accumulation of such pollutants (Ellis et al, 2020). Therefore, the use of shark species as bio indicators has been underlined by numerous investigators for environmental monitoring studies (Adel et al 2018;Lozano-Bilbao et al 2018;Kim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angel sharks often occupy coastal waters and thus exposed to different contaminants, the high trophic level of this environment could increase the accumulation of such pollutants (Ellis et al, 2020). Therefore, the use of shark species as bio indicators has been underlined by numerous investigators for environmental monitoring studies (Adel et al 2018;Lozano-Bilbao et al 2018;Kim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of Hg are not found at levels that would exceed most current guidelines for seafood products in the former studies on the other angelshark species, S. californica and S. squatina (Morris et al 1989;Escobar-Sánchez et al 2016). Ellis et al (2020) reported that there is no report on the contaminants that have impacted on angel sharks, and further studies are required on the potential impacts of habitat degradation and water quality for inhabiting areas of angel shark, especially industrialized areas. Therefore, the present nding with exceeded legalized limit of Hg concentrations are very valuable for the conservation and sustainability of S. aculeata as management consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the detailed distribution of both species along the EPO remains uncertain, especially in the areas of North of South America where both species have been reported [14,15,18,44]. Additionally, angel sharks are target species and are captured by small-scale fisheries [28]. However, reports of landings are rather general and likely include several species of angel sharks, thus molecular tools could serve well for the accurate identification of the species landed, their distributions, and the fisheries with which they interact [28].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, angel sharks are target species and are captured by small-scale fisheries [28]. However, reports of landings are rather general and likely include several species of angel sharks, thus molecular tools could serve well for the accurate identification of the species landed, their distributions, and the fisheries with which they interact [28].…”
Section: Introductionmentioning
confidence: 99%